A randomised, family-focused dietary intervention to evaluate the Atlantic diet: the GALIAT study protocol. (December 2016) - Calvo-Malvar, Maria del Mar; Leis, Rosaura; Benítez-Estévez, Alfonso; Sánchez-Castro, Juan; Gude, Francisco
Abstract Background The traditional diet of northwestern Spain and northern Portugal follows an 'Atlantic diet' pattern. Adherence to the Atlantic diet has been related to the good metabolic health and low coronary mortality recorded for these regions. Methods The GALIAT (Galicia Alimentación Atlántica [Galicia Atlantic Diet]) study is a randomised, controlled, dietary intervention clinical trial designed to examine the effect of the Atlantic diet on the lipid profile, glucose metabolism, inflammation makers and adiposity of the general population. The trial involved 250 randomly selected families (715 adults and children over 3 years of age) from a town in Spain's northwest, randomly allocated to follow either a control diet (C group) or the Atlantic diet (AD group) for a period of 6 months. The families of the AD group received educational sessions on food, diet and gastronomy and were provided written supporting material with nutritional recommendations and recipes for the preparation of menus. They also attended cooking classes. Throughout the study period, these families were provided a range of foods (free of charge) that form part of the traditional Atlantic diet. The C group families took part in none of the above activities, nor were they provided with any food. Lipid profile variables (primary variables), and anthropometric, inflammation marker and glucose metabolism status (secondary variables), were measured at baseline, three and six months. Discussion The GALIAT study is the first clinical trial to examine the effects of the Atlantic diet on metabolic and cardiovascular health and adiposity. If the study hypothesis is confirmed, this dietary pattern could be included in strategies to promote health. Trial registration ClinicalTrials.gov, NCT02391701 on March 18, 2015.